Designing for Quality of life. (July 2020) - Uysal, Muzaffer; Berbekova, Adiyukh; Kim, Hyelin
Abstract: There has been substantial interest in examining the connection between tourism as a socioeconomic force and quality of life. Similarly, designing places as smart destinations to enhance experience is now an important area of research and application. The paper argues that designing for tourism is intimately related to the enhancement of quality of life; that is, designing appropriate platforms for tourism experience settings with its actors will contribute not only to the wellbeing of participants, but also improve the livability of places as destinations. The article outlines a conceptual framework with seven propositions which links tourism design and key elements of quality of life. The paper concludes with a discussion of important areas for future research and practical implications. Highlights: Limited research on the connection between designing for tourism and quality of life (QoL) Importance of supply-demand interaction in experience design for QoL Co-creation of experience and use of both operant and operant resources in designing for QoL Importance of technology in designing for QoL Motivation of designing experience and destination as facilitators of quality experience